Art installation - the charging heart - Gou, Shuang (Stimulus: A Medical Humanities Journal, 2023)
It is 29 inches in height and 13 inches in width and is made of iron wire, 3D printing, lights, electrical wires, and an control panel. Here the heart is a symbol of man’s mental state. Charging is a metaphor. I feel that people just feel like out of power sometimes. They need something to make them "alive" again. It’s like a battery needs recharging. I want to talk about the issue in the fast-paced modern world of how people can balance their life and where they can refuel their energy. It is important to me because I was often bothered by this issue at that time. Working under high intensity and pressure, I often feel a lack of energy source. The fountain of life and inspiration seems to be drying up. But I can find nowhere to give a supplement. I want the observer to see the object and think about the connection with themselves, when do they need the power in their mental world and what the power is for them.